1975
DOI: 10.1021/bi00687a025
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradative ornithine decarboxylase of Escherichia coli. Purification, properties, and pyridoxal 5'-phosphate binding site

Abstract: The biodegradative ornithine decarboxylase of Escherichia coli has been purified to apparent homogeneity. At its pH optimum (pH 7.0), the enzyme exists as a dimer of 160,000 molecular weight. Aggregation of the dimer was promoted by lower pH values. The enzyme requires pyridoxal 5'-phosphate for activity. The coenzyme appears to be bound in Schiff base linkage as suggested by spectral studies and inhibition by NaBH4. The following sequence was determined for the coenzyme binding site: Val-His-(epsilon-Pxy)Lys-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…Second, if internal pH were considerably higher than our measurements indicated, then other amino acid decarboxylases with higher pH optima, such as ornithine decarboxylase (pH optimum 7.0), might be expected to function as effective acid resistance systems. However, ornithine decarboxylase does not protect cells at pH 2.5, a finding we attribute to the high pH optimum limiting enzymatic function at the acidic internal pH reported here (3,22). The situation with lysine decarboxylase (CadA) further supports the hypothesis.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Second, if internal pH were considerably higher than our measurements indicated, then other amino acid decarboxylases with higher pH optima, such as ornithine decarboxylase (pH optimum 7.0), might be expected to function as effective acid resistance systems. However, ornithine decarboxylase does not protect cells at pH 2.5, a finding we attribute to the high pH optimum limiting enzymatic function at the acidic internal pH reported here (3,22). The situation with lysine decarboxylase (CadA) further supports the hypothesis.…”
Section: Discussionsupporting
confidence: 70%
“…Carbonic anhydrase essentially adds water, not free protons, to CO 2 to make carbonic acid (H 2 CO 3 ); carbonic acid can then dissociate to HCO 3 Ϫ and H ϩ . Because the pK a of this reaction is 6.5, an internal pH that is estimated to be between 4.2 and 4.7 will prevent this dissociation (18).…”
Section: Discussionmentioning
confidence: 99%
“…Degradative basic amino acid decarboxylation systems are quite common among Gram-negative Enterobacteriaceae, where they play a role in acid stress resistance (34,35,36). Different systems consisting of a decarboxylase and a precursor/product exchanger have been found for lysine/cadaverine (LDC) (cadAB), arginine/ agmatine (adiAC), and ornithine/putrescine (ODC) (speF/potE).…”
Section: Discussionmentioning
confidence: 99%
“…For assay of inducible ornithine decarboxylase, cell extracts were obtained from 100 ml cultures grown in the medium described by Applebaum et al (1975). Bacteria were collected, washed and then resuspended in 1 ml of 0.05 M-Mes buffer, pH 6.3, containing 1 mM-dithiothreitol and 2.4 mM-EDTA.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Several studies on the decarboxylation of ornithine and arginine have indicated that each of these reactions can be catalysed by two different enzymes: one is a constitutive 'biosynthetic' decarboxylase present in cells grown in neutral minimal medium, and the other is a 'biodegradative' enzyme induced in certain strains cultivated in acid media containing high concentrations ofthe respective undecarboxylated substrate, ornithine or arginine (Gale, 1946;Morris & Fillingame, 1974;Applebaum et al, 1975Applebaum et al, , 1977.…”
Section: Introductionmentioning
confidence: 99%